Fungal Inhibition of Agricultural Soil Pathogen Stimulated by Nitrogen-Reducing Fertilization - Shen, Min-Chong; Shi, You-Zhi; Bo, Guo-Dong; Liu, Xin-Min (Frontiers in Bioengineering and Biotechnology, 2022)
Plant health is the fundamental of agricultural production, which is threatened by plant pathogens severely. The previous studies exhibited the effects of different pathogen control strategies (physical, chemical and microbial methods), which resulted from bringing in exogenous additives, on microbial community structures and functions. Nevertheless, few studies focused on the potential inhibitory abilities of native microbial community in the soil, which could be activated or enhanced by different fertilization strategies. In this study, three plant disease (TMV, TBS, and TBW) of tobacco, fungal community of tobacco rhizosphere soil, and the correlation between them were researched. The results showed that nitrogen-reducing fertilization strategies could significantly decrease the occurrence rate and disease index of three tobacco diseases. The results of bioinformatics analyses revealed the fungal communities of different treatments could differentiate the nitrogen-reducing fertilization group and the control group (CK). Furthermore, key genera which were responsible for the variation of fungal community were explored by LEfSe analysis. For instance, Tausonia and Trichocladium increased, while Naganishia and Fusicolla decreased, under the nitrogen-reducing fertilization conditions. Additionally, the correlation between tobacco diseases and key genera was verified through the mantel test. Moreover, the causal relationship between key genera and tobacco diseases was deeply explored by PLS-PM analysis. These findings provide a theoretical basis for a nitrogen-reducing fertilization strategy against tobacco diseases without exogenous additives, and make contributions to revealing the microbial mechanism of native-valued fungal key taxa against tobacco diseases, which could be stimulated by agricultural fertilization management.